2013
DOI: 10.1080/19407963.2012.734991
|View full text |Cite
|
Sign up to set email alerts
|

Climate change mitigation policy and the tourism sector: perspectives from the South West of England

Abstract: Climate change is one of the major challenges of our times and state intervention has been identified as a critical success factor in attempts to tackle it. This paper critically explores the reciprocal relationship between climate change policy and the tourism sector in the United Kingdom. It examines on the extent to which current mitigation activities within accommodation businesses in the South West of England reflect recent UK policy on climate change as well as the prospects of the tourism sector contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Context, it was argued, ultimately determined their productiveness, efficiency and cost effectiveness (in terms of payback), not to say their ability to contribute towards emissions reductions (in that order). The more perceptive in Stage Two even contended that renewable energy had become synonymous with solar energy because of high profile public discourse in the UK about the Feed-in-Tariff (see Coles et al 2013). However, other renewable energy options were perhaps more suitable to older buildings.…”
Section: Discussionmentioning
confidence: 99%
“…Context, it was argued, ultimately determined their productiveness, efficiency and cost effectiveness (in terms of payback), not to say their ability to contribute towards emissions reductions (in that order). The more perceptive in Stage Two even contended that renewable energy had become synonymous with solar energy because of high profile public discourse in the UK about the Feed-in-Tariff (see Coles et al 2013). However, other renewable energy options were perhaps more suitable to older buildings.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this stage have been reported in detail elsewhere (Coles et al 2013;Coles, Zschiegner and Dinan 2014;Coles, Dinan and Warren 2014). Of relevance here is that there was no significant difference in the number of, and level of total investment in, pro-environmental innovations among properties of different age.…”
Section: Methodsmentioning
confidence: 57%
“…More specifically here, their work resonates with the challenges faced by those owning or managing older buildings in responding to climate change. Difficulties in retrofitting, establishing the necessary levels of investment and determining payback periods, as well as planning, regulation and governance are common are common to the latter Baldock 2008, 2009;Chan 2011;Coles, Zschiegner and Dinan 2013). Yet, just as historic premises have been largely overlooked in research on heritage tourism, so too they have been in discourse on tourism and climate change (Gössling, 2010;Kaján & Saarinen 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Just as the previous study suggested that an evaluation of tourism policy is needed to reduce economic growth as a result of tourism development that affects aspects of sustainability [8]. On the other hand, the evaluation of tourism policies can sustain business development, when climate change becomes a serious problem affecting tourism sustainability [9]. In addition, the importance of evaluating tourism policies and their impacts on social and cultural aspects [10].…”
Section: Introduction *mentioning
confidence: 99%